2014
DOI: 10.1177/0920203x14532224
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic identity and racial contestation in cyberspace: Deconstructing the Chineseness of Lou Jing

Abstract: This article examines Chinese cyberspace debates over the racial and national identity of a television show contestant Lou Jing, a biracial woman of Chinese and African American descent. We argue that the online commentary about her offers a productive entry point into contemporary Chinese cultural struggles over race. In particular, we consider how the Internet and other digital communication technologies are being mobilized as discursive sites for articulations of Chinese anti-black racism, as well as discur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Studies have found that negative perceptions of African Americans among AAAUS are often based on negative stereotypes circulated throughout various media outlets in the United States depicting them as “welfare dependent,” “aggressive,” and “deviant” (Lee and Ulmer 2000; Johnson 2007; Park et al 2006). Consequently, African Americans have been the target of several discriminatory and racially driven incidents based on these negative stereotypes held by Chinese and Korean people (Cheng 2011; Frazier and Zhang 2014; Johnson 2007; Sautman 1994).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have found that negative perceptions of African Americans among AAAUS are often based on negative stereotypes circulated throughout various media outlets in the United States depicting them as “welfare dependent,” “aggressive,” and “deviant” (Lee and Ulmer 2000; Johnson 2007; Park et al 2006). Consequently, African Americans have been the target of several discriminatory and racially driven incidents based on these negative stereotypes held by Chinese and Korean people (Cheng 2011; Frazier and Zhang 2014; Johnson 2007; Sautman 1994).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While it is not the aim of this article to offer an analysis of this historical construction, it is important to note that the more recent literature engaging with the notions of "race" and "racism" in Africa-China relations (see Sautman andYan 2007, 2009;Shen 2009;Cheng 2011;Bodomo 2012;Monson and Rupp 2013;Frazier and Zhang 2014;Galtung and Stenslie 2014;Lan 2014Lan , 2015Lan , 2016Lan , 2017Pfafman, Carpenter, and Tang 2015;Moyo 2016;Li 2017;Huynh and Park 2019) often sets out the following historical stages as a basis for their argumentation: (1) China's pre-modern encounters with blacknesses; (2) the arrival of the notion of "race" and its sinification; (3) the racial thinking turn under internationalism; and (4) post-socialist configurations of racial thinking. Below, I briefly review these stages.…”
mentioning
confidence: 99%
“…The internet has contributed particularly to the diversification of nationalistic consciousness and become an important channel 'by which the most globalised segment of the Chinese population, namely, educated urban youths, expresses the multifaceted discourse' of nationalism (Zhao, 2007: 193-197). The extreme right end of nationalistic internet users have been drawn to cyber-racism (Chang, 2011;Frazier and Zhang, 2014) and Han supremacism (Leibold, 2010;. The former reinforces globally imagined racial hierarchies and the latter applies a similar binary of progress and backwardness to the relationship between the Han majority and ethnic minorities within China.…”
Section: From Cyber-nationalism To Right-wing Populism Onlinementioning
confidence: 99%